Histological studies on the exocrine portion of pancreas of the domestic duck (Anas boschas domesticus)* - MADHAVI, G; CHANDRASEKHARA RAO, T S; KUMAR, D PRAMOD; NAGAMALLESWARI, Y; SREENU, M (The Indian Journal of Animal Sciences, 2013)
Lobulation was not evident in pancreas of the duck. Three types of acinar cells I.e resting, active and exhausted were identified in a section of pancreas based on the nuclear and cytoplasmic appcarance. The nucleus increascd in size while the chromatin material diminished and the nucleolus became larger and more deeply stained from the resting state through active state to exhausted state. The zymogen granules were abundant in resting celis, moderate in active cells and least in exhausted cells. The acini emptied into mtenncdiate tubules through intercalated ducts both of which were lined by simple squamous epithelium. The larger ducts were lined by Simple cuboidal epithelium while the extraglandular ducts showed tunica mucosa, tunica musculans and tunica adventitia. Their fold cd mucosa was lined by simple columnar epithelium.